1984
DOI: 10.1007/bf01438363
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of196,198Pt and202,204Hg with the (d, pn?) reaction

Abstract: Gamma-ray and conversion electron spectra were measured in the reaction of 25 MeV deuterons on 174yb, 196'19apt, 2~176 and 132Th. The (d, pxn) deuteron break-up reactions were studied by the measurement of py-and 77-coincidences. Levels with spins up to approximately 10h are observed in the (d, pn) reactions, with a strong preference of the population of yrast states. In the Pt and Hg nuclei the ground bands are seen up to the 6 + states and in 196,198pt the semi-decoupled 5-, 7-, and 9-yrast levels are pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The transition which is expected to have the highest intensity, 3 + ~ 2] at 327 keV, could not be evaluated due to a contamination by the 2~--*0[ transition of 194pt at 328 keV. In the angle-integrated spectra we observe a line at EV=594 keV which has been seen by Schiller et al [27] in coincidence with the 3~ ~22+ transition and been suggested to be the 5[ ~ 3[ transition. We can support this assumption by qualitative arguments: the observed intensity agrees well with model predictions for the 51+ ~ 3[ transition, and the measured gamma multiplicity corresponds to the expected value.…”
Section: Iiia the Ground State Band And The ? Bandmentioning
confidence: 60%
See 3 more Smart Citations
“…The transition which is expected to have the highest intensity, 3 + ~ 2] at 327 keV, could not be evaluated due to a contamination by the 2~--*0[ transition of 194pt at 328 keV. In the angle-integrated spectra we observe a line at EV=594 keV which has been seen by Schiller et al [27] in coincidence with the 3~ ~22+ transition and been suggested to be the 5[ ~ 3[ transition. We can support this assumption by qualitative arguments: the observed intensity agrees well with model predictions for the 51+ ~ 3[ transition, and the measured gamma multiplicity corresponds to the expected value.…”
Section: Iiia the Ground State Band And The ? Bandmentioning
confidence: 60%
“…Later, Schiller et al [27] suggested this state to be the expected 4~--level, because in a (d, pnv) experiment a transition of 521 keV was observed in coincidence with the 31 + ~ 22+ transition which was assigned the 4~ ~ 3~ transition. We could not see this line because of the strong 4[ ~ 2~ transition of the same energy.…”
Section: Iiid the 4+ Statementioning
confidence: 94%
See 2 more Smart Citations
“…However, the 7-ray directly depopulating the isomeric level could not be identified, and Maier et al therefore suggest the existence of an unobserved low-energy 13/2 + ~ 9/2-M2 transition. In a previous investigation [2] we had found, that levels in 2~ are populated with appreciable cross section in the 2~ (d, p) deuteron break-up reaction. We have therefore carried out a more extended study of 2~ in this reaction, in order to identify the v i13/2 level.…”
Section: Introductionmentioning
confidence: 97%